Eligibility Criteria in Advanced Urothelial Cancer Clinical Trials: An Assessment of Modernization and Inclusion - Benjamin D. Mercier; Ameish Govindarajan; Daniela V. Castro; Xiaochen Li; Errol J. Philip; Matthew I. Feng; Sweta R. Prajapati; Elyse H. Chan; Kyle O. Lee; Ishaan Sehgal; Jalen Patel; Anna O'Dell; et al. (Cancer Medicine)
ABSTRACT Introduction In a joint statement, Friends of Cancer Research and the American Society of Clinical Oncology affirmed the need for broadening clinical trial eligibility criteria to expand patient access to investigational treatments and enroll cohorts more representative of the general population. Our study aimed to characterize and analyze the prevalence of overly exclusionary eligibility criteria in contemporary clinical trials involving patients with locally advanced and metastatic urothelial cancer. Methods Utilizing MeSH query terms “(metastatic OR advanced OR stage IV OR unresectable) AND (bladder cancer OR upper tract urothelial carcinoma OR upper tract urothelial cancer)” in ClinicalTrials.gov, we identified 205 interventional urothelial cancer trials activated between June 30, 2012 through June 30, 2022. We investigated the prevalence of four potentially restrictive criteria: the presence of brain metastases, HIV infection, hepatitis B/C infection, and the presence of concurrent malignancies. Fisher's Exact test was utilized to ascertain significant associations between criteria and trial characteristics. Results Of 205 trials found initially, 37 (18%) contained sufficient data for analysis. Overall, HIV infection and Hepatitis B/C infection were most restrictive, with most trials completely excluding patients with these conditions (89.2%; 56.8%). Restrictiveness for HIV infection and type of therapy were significantly associated, with most exclusionary trials involving combination or immunotherapies (39.4%; 33.3%; p = 0.003). Brain metastases were totally excluded by 35.1% of trials and had 18.9% of trials provide no explicit criteria or guidelines. Most trials specified conditions for the inclusion of patients with concurrent malignancies (91.9%). Variant histology was also underrepresented, with most trials not specifying or totally excluding all variant histology (43.2%; 8.1%). Conclusion HIV infection and hepatitis B/C infection were commonly identified in exclusion criteria across these trials despite limited evidence suggesting these criteria significantly impact therapy efficacy and tolerability. Broadening and modernization of eligibility criteria will ensure more inclusive clinical trials.